Assembly language programming for the 80386 - Fernandez, Judi N. (McGraw-Hill Pub., 1990)
The authors provide a comprehensive guide to Assembly language for the Intel 8086 family through to 80386. The programmer reading this book will be able to write efficient assembly programs, understand extended and protected mode, and be familiar with Microsoft's Macro Assembler.